Phosphoglucomutase Is Not the Target for Galactose Toxicity in Plants - Althammer, Martina; Blöchl, Constantin; Reischl, Roland; Huber, Christian G.; Tenhaken, Raimund (Frontiers in Plant Science, 2020)
Plants synthesize a number of different oligomeric or polymeric sugars containing galactose. During growth and development some of these carbohydrates are metabolized or remodeled releasing galactose as a breakdown product. All plants have established recycling pathways for such sugars, for which they seem to have a limited capacity to cope with. Exceeding these limits results in sugar toxicity, which is observed already at concentrations as low as 1 mmol·L-1 for galactose. The mechanism of galactose toxicity is poorly understood but it seems plausible that the enzymes involved in carbohydrate metabolism also might be the targets responsible for the adverse effects. Data from yeast and bacteria suggests that the enzyme phosphoglucomutase (PGM) is inhibited by galactose-1-phosphate. To test this hypothesis for plants we expressed recombinant cytosolic PGM3 from Arabidopsis in E. coli. Intriguingly, the enzyme was not inhibited by galactose-1-phosphate at physiological concentrations. Furthermore, PGM3 did not convert galactose-1-phosphate to galactose-6-phosphate, which was suggested as the inhibitory mode of action in yeast. In addition, metabolite levels in Arabidopsis roots were analyzed for their galactose-1-phosphate concentration by means of GC-MS. Seedlings grown on MS-media with sucrose contained less than 10 nmol·g FW-1 of galactose-1-phosphate. However, seedlings from plates, in which the sucrose was replaced by galactose, showed a strong increase of Gal-1-P to levels of up to 200 nmol·g FW-1.